American injustice: inside stories from the underbelly of the criminal justice system - Rudolf, David S. (Custom House, 2022)
"From the fearless defense attorney and civil rights lawyer who rose to fame with Netflix's The Staircase comes an essential examination of America's corrupt and abusive criminal justice system"--